Elevated plasma aldosterone levels are associated with a reduction in retinal ganglion cell survival. (August 2018) - Takasago, Yukari; Hirooka, Kazuyuki; Nakano, Yuki; Kobayashi, Mamoru; Ono, Aoi
Objective: The purpose of this article is to investigate the relationship between the plasma concentration of aldosterone and changes in the number of retinal ganglion cells (RGCs) after systemic administration of aldosterone. Methods: An osmotic minipump that was subcutaneously implanted into the midscapular region of rats administered 40, 80 or 160 μg/kg/day aldosterone or vehicle. Enzyme immunoassay kits were used to measure the plasma aldosterone concentrations two weeks after the systemic administration of aldosterone or vehicle. Six weeks after these systemic administrations, the number of RGCs was measured. Results: The plasma aldosterone concentrations at two weeks after systemic administration of vehicle or 160 μg/kg/day aldosterone were 238 ± 17 pg/ml and 1750 ± 151 pg/ml (748.5% ± 183.2%), respectively. There was a significant decrease in the number of RGCs in the central retina of the rats after the administration of either 80 or 160 μg/kg/day aldosterone. In the peripheral retina, however, there was a significant decrease in the number of RGCs in 40, 80 or 160 μg/kg/day aldosterone. There was a significant correlation between the number of RGCs and plasma aldosterone concentration. Conclusions: After systemic administration of aldosterone, there was a negative correlation between the plasma aldosterone concentration and the number of RGCs.